The metamorphosis of punishment in the light of social interest motivations (Academic Journal of Internal Affairs, 2019)
The article presents the social theoretical, psychological phenomena and interactions in the crime-punishment context, which have played historical role in framing perceptions of punishment. Briefly describes the psychology of crime and the role of public opinion in the evolution of crime’s perception.
Keywords: forms of punishment; crime; psychology; iterpersonal interaction